Association between AzoFert (R) and efficient microorganism potentiates the growth and productivity of beans - Calero Hurtado, Alexander [UNESP] (2020)
To evaluate the association hetii een Azol'ert 10 and efficient microorganisms (IC\1) in the morphological and productiie response of common bean in three sO\'ing season three experiments were developed at the Collective farmer Martires de Taguasco', Sancti Spiritus. Cuba, from September 2014 to April 2015. The treatments evaluated ivere the absolute Control: without inoculating and without fertilizing. foliar applications of l'l (100 mgI;1), inoculation of the seeds ith -\zoVert 10 (108 cfu g i) and the associate between AzoLert 10 + Ef\1 The indicators evaluated were the height of the plants (cm), the number of leaves per plant, legumes per plant, grains per plant mass of 100 grains (g) and yield tha). The results showed that the treatments iith EM, \zoVert 10 and the association between \zoEert R + EM achieved higher responses of the morphological and productive indicators on the intermediate so'.' ing period (LI) in comparison to earl3 (LT) and late season (LA). The Azol'ert 10 + EM association treatments showed better performance compared ivith the individual application of L1ł and AzoVert 10 also increase the indicators ci aluated and the ield was higher 1 02% in early season 1 13% in the intermediate and 111 % in the late season in relationship to absolute control. 'l'he findings established the potentiality of the association of Azol'ert 10 + l\ll' as an efficient alternative to increase bean productiit and could potentially lead to sustained increase in crop ield